Minangkabau Trace in Oil City: The History of Minangkabau Migrants and Social-Economic Life in Duri City, Riau Province (1961-2024) - Fahrezi, Farel; Midawati, Midawati (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This study aims to relate the historical phenomena of Minangkabau migrants from West Sumatra in Duri City of Riau Province, 1961-2024, to the socio-political and socio-economical developments that caused migration and resettlement. Data collection involves the historical method (heuristics, source criticism, interpretation, and historiography), and primary research involves archives, population data, journal articles, testimonies from Minangkabau Duri migrants, and Duri elders in the Mandau District. The results of this study indicate that the socio-political and socio-economical developments that cause migration and resettlement are two different levels. Large scale migrations per PRRI-caused political tension and subsequent economic hardship - and patterns of migration in 1958. Development of the PT Caltex Duri Oil and subsequent oil fields represent the most immediate push and pull factors to migrate and resettle as advancements to avoid deterrents and new employment opportunities emerged. Accordingly, Duri became and continues to be a multi-ethnic industrial town filled with changes of eras that Minangkabau migrants successfully adapted to - while maintaining cultural continuity through language, Minangkabau customs, and associated community-based organizations. They contributed to trade, education, services, and oil, furthering Duri's socio-economics. Yet despite a multicultural atmosphere, strong attachment to emotion and culture remains at home. This study connects armed conflict to oil advancements and cultural attachment for the Minangkabau diaspora and modern Duri City socio-economically transformed.